Cameroon Econoic Update, January 2013, No. 5 : Mitigating Poverty, Vulnerability, and Risk--A Special Focus on Social Safety Nets - World Bank (Washington, DC, 2014)
The economic updates aim to share knowledge and stimulate debate among those interested in improving the economic management of Cameroon and unleashing its enormous potential. The notes thereby offer another voice on economic issues in Cameroon, and an additional platform for engagement, learning and change. Cameroon's overall poverty rate has not declined and has even increased in the poorest regions. Food security is also problematic in those regions. Yet, Cameroon has a number of small-scale and ad hoc safety net programs which are not appropriately designed to address either chronic or transient poverty. Too few resources are put into these programs for the moment to make a real difference with most of these limited resources allocated to emergency initiatives. Social safety nets build households' productive assets and expand their income-earning opportunities by building their skills and enabling them to engage in higher risk and higher return activities. Going forward, in addition to continued efforts to foster faster economic growth, an efficient, equitable, and financially-sustainable social safety net strategy should be developed that combines different forms of interventions to deal with the specific needs of the poor and the vulnerable, and includes an effective monitoring system to improve the quality programs.